Identity inclusiveness and centrality: investigating identity correlates of attitudes toward immigrants and immigration policies - Espinosa, A. (2018)
Social psychology highlights ingroup identity as an important determinant of intergroup attitudes and relations; however, research has demonstrated that its effects can be positive, negative, or nonexistent depending on how such identity is conceptualized. This research explores how national identity inclusiveness (Study 1) and centrality (Study 2) are associated with immigration related attitudes in school and countrywide settings, respectively. Study 1 showed that teachers’ inclusive (i.e., overlapping) identities regarding their immigrant students related to positive attitudes toward these students, but not to attitudes about immigrants in general or immigration policy preferences. Study 2 found that national identity centrality was related to negative attitudes toward the social impact of immigrants, and to higher support for policies inhibiting the social inclusion of immigrants in the receiving community. Combined, these studies highlight the importance of considering different conceptualizations of ingroup identity in identifying relations to immigration‐based attitudes. Moreover, the studies highlight the value of promoting inclusive identities when aiming to improve attitudes toward immigrants. We conclude by discussing a new approach for promoting inclusive identities by framing immigrants as indispensable to the receiving community.